Evanescent-wave cavity ring-down spectroscopy applied to electrochemical ion transfer at liquid-liquid interfaces - Colqui Quiroga, Mónica Vanesa (2012)
Cavity Ring-Down Spectroscopy has been successfully applied to investigate liquid-liquid interfaces in an electrochemical environment. It has been demonstrated that this technique is very sensitive to detect changes in the concentration of species at the interface which absorb at the incident wavelength. Thus, we have shown that this technique can be employed to follow diverse processes at liquid-liquid interfaces involving concentration changes produced by the applied potential. In our contribution, we show for the first time a spectroscopic response of Evanescent Wave Ring-Down Spectroscopy directly originated by charging/discharging processes and ion transfer at the electrochemical double layer of a liquid-liquid interface. © 2012 Elsevier B.V. All rights reserved.